Patis by acid hydrolysis process - Cua, Benito S.
"Patis", a very popular condiment in the Philippines, prepared locally by the fermentation of small fishes such as tunsay dilis, and small shrimps, can be manufactured by hydrolysis of the fish with concentrated HCl. By this new process, any kind of fish meat can be converted into patis. In contrast to the fermentation method, this new acid hydrolysis process can utilize any kind of fish meat, including fish meal. Furthermore, this method can be accomplished within a few hours, in contrast to the four or five months time required for the fermentation method. There is almost no detectable difference in odor, taste, color, and clarity of the patis made by this method and that made by the fermentation process. Furthermore, the quality of the product can be standardized by using Roce?s nitrogen partition method. Therefore, the acid hydrolysis method obviously lends itself much better to quality control.